2014
DOI: 10.1186/1742-4690-11-s1-p118
|View full text |Cite
|
Sign up to set email alerts
|

The antisense protein of HTLV-2 positively modulates HIV-1 replication

Abstract: Unlike HTLV-1, HTLV-2 does not induce leukemia and has been tentatively associated with an HTLV-1-associated myelopathy-like disorder. It has been reported that HTLV-2/HIV-1 co-infected patients progress less rapidly to AIDS than HIV-1-infected individuals. Tax2 has been suggested to mediate this protective state by inducing MIP-1α expression and blocking HIV-1 infection. As cells from HTLV-2-infected individuals mainly express Antisense Protein 2 (APH-2), our objective was to determine if this protein might a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…In 1988, Miller [ 96 ] made the observation that there was also potential to encode a peptide product from an RNA transcribed from the minus strand of the provirus. Since then, there have been a number of reports providing evidence for predicted RNA and protein products from the minus strand in HIV-1 [ 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ], SIV [ 107 ], FIV [ 108 ], and in the deltaretrovirus, BLV [ 109 ]. In FIV, there are several potential short open reading frames that may be translated from a negative strand message.…”
Section: Fiv As a Molecular Analogue To Hivmentioning
confidence: 99%
“…In 1988, Miller [ 96 ] made the observation that there was also potential to encode a peptide product from an RNA transcribed from the minus strand of the provirus. Since then, there have been a number of reports providing evidence for predicted RNA and protein products from the minus strand in HIV-1 [ 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ], SIV [ 107 ], FIV [ 108 ], and in the deltaretrovirus, BLV [ 109 ]. In FIV, there are several potential short open reading frames that may be translated from a negative strand message.…”
Section: Fiv As a Molecular Analogue To Hivmentioning
confidence: 99%
“…We also observed that there is a reduction in the expression of both proteins when they are transfected together, as compared to the protein expression when they are transfected individually. To the best of our knowledge, only one prior study by Torresilla et al [ 23 ] investigated the role of APH-2 in HIV-1 replication. The authors reported increased MIP1α levels along with the inhibition of NF-kB and NFAT in the presence of APH-2, but observed positive modulation of full-length HIV-1 luciferase expression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one prior study by Torresilla et al [ 23 ] investigated the role of APH-2 in HIV-1 replication. The authors reported increased MIP1α levels along with the inhibition of NF-kB and NFAT in the presence of APH-2, but observed positive modulation of full-length HIV-1 luciferase expression [ 23 ]. Even though the study reported increased expression of MIP1 α, downregulation of NF-kB and NFAT supposedly supports the negative role of APH-2 on HIV-1 replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1988, Miller [92] made the observation that there was also potential to encode a peptide product from an RNA transcribed from the minus strand of the provirus. Since then, there have been a number of reports providing evidence for predicted RNA and protein products from the minus strand in HIV-1 [93][94][95][96][97][98][99][100][101][102], SIV [103], FIV [104], and in the deltaretrovirus, BLV [105]. The use of neurovirulent strains of FIV has also allowed for the investigation of neuropathogenic effects on the peripheral nervous system (PNS) as a model of HIV distal symmetric polyneuropathy (DSP), demonstrating rapid onset of peripheral neuropathy in FIV infected cats with axonal injury, macrophage activation, and detection of virus within the nerve [50,132].…”
Section: Fiv As a Molecular Analogue To Hivmentioning
confidence: 99%